Legal Protection for Taxpayer Proxy in View of MK Decision No.63/Puu-Xv/2017 - Mochamad Ferdiansa; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the duties of the state is to improve the common welfare. Significant financial resources are required to carry out their duties, these costs may be covered by tax collection. Taxes are levied not only on individuals, but also on legal entities that are taxed under the law and are referred to as taxpayers. Taxpayers not only have obligations in the taxation system, but also rights. The application of rights and obligations is often avoided for various reasons. So that the Directorate General of Taxes can improve by issuing a power of attorney to carry out its rights and obligations. At first, the issuance of a power of attorney was very helpful, but with changes in regulations, the issuance of a power of attorney caused problems, namely that everyone's rights were limited. Based on this description, this journal was written to answer two problems, namely the arrangement for the appointment of tax authorities in Law Number 28 of 2007 concerning amendments to Law Number 6 of 1983 concerning General Provisions and Tax Procedures, and Regulations for granting power of attorney after a decision is made. Constitutional Court No. 63/PUU-XY/2017